Treatment Outcome Evaluation in Therapeutic Communities in the Czech Republic: Alcohol Consumption and Other Results One Year After Discharge. Issue 1 (2nd January 2018) - Šefránek, Martin; Miovský, Michal
ABSTRACT: The aim of this article is to investigate changes in alcohol consumption among predominantly methamphetamine users (N = 176) in four residential therapeutic communities for addiction treatment in the Czech Republic. This is a quantitative prospective, naturalistic, cohort study that compares drinking patterns, illicit drug use, injecting, and crime prior to treatment and one year after discharge. The response rate at follow-up was 77.8% (N = 137). At the one-year follow-up the number of excessive drinkers was significantly reduced from 51.1% to 31.4%. The rate of abstinence from alcohol (33.6%) and moderate drinking (35%) at follow-up was not significantly different from the pretreatment level. At the one-year follow-up, 33.6% were consuming no alcohol, whereas 88.3% reported abstinence from methamphetamine. The authors conclude that one year after discharge from the treatment most clients were abstinent from illicit drugs. However, the number of clients who were abstinent from alcohol remains low. The implication for treatment and further research is discussed.